2002
DOI: 10.1159/000063150
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction for Diagnosis of Cutaneous Leishmaniasis in Histologically Positive, Suspicious and Negative Skin Biopsies

Abstract: Background: Cutaneous leishmaniasis (CL) is a major problem in many tropical and subtropical countries. The clinical diagnosis should be confirmed by identification of the parasite in biopsy or smear or by tissue culture. The sensitivity of direct microscopy is not high, and tissue culture is not uniformly available and successful. Polymerase chain reaction (PCR) is a sensitive test for the detection of low amounts of DNA in tissues. Objective: We applied PCR on paraffin-embedded skin biopsies to assess the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 11 publications
10
53
2
3
Order By: Relevance
“…Conventional and real-time PCR assays for the diagnosis of CL have demonstrated greater sensitivity than microscopy or parasite culture (130,391,516). PCR performed on DNA extracted from paraffin-embedded tissues is also useful for the diagnosis of CL (490).…”
Section: Leishmaniamentioning
confidence: 99%
“…Conventional and real-time PCR assays for the diagnosis of CL have demonstrated greater sensitivity than microscopy or parasite culture (130,391,516). PCR performed on DNA extracted from paraffin-embedded tissues is also useful for the diagnosis of CL (490).…”
Section: Leishmaniamentioning
confidence: 99%
“…Furthermore, Medeiros et al (2002) using the same primers found positivity in 81.5% of the examined samples by PCR, with a specificity of 100%, while the histological test was positive in 50% of the cases. Safei et al (2002) found a sensitivity of 92% in the diagnosis of cutaneous leishmaniasis in paraffin-embedded biopsies using PCR, and a specificity of 100%.…”
Section: Discussionmentioning
confidence: 96%
“…Real-time PCR has clear advantages over microscopy in the detection and speciation of leishmaniasis. [49][50][51] The PCR-based assays used in our study yielded rapid and accurate information on speciation that was used in a timely fashion to inform choice of therapy. Several PCR-based assays for the diagnosis of leishmaniasis have been developed to date.…”
Section: Discussionmentioning
confidence: 99%